2016
DOI: 10.5901/ajis.2016.v5n2p35
|View full text |Cite
|
Sign up to set email alerts
|

Rural Road Infrastructural Challenges: An Impediment to Health Care Service Delivery in Kabba-Bunu Local Government Area of Kogi State, Nigeria

Abstract: In spite of the diverse rural development policy programmes designed address improvement in the condition of rural dwellers in Nigeria, the health needs of many of the rural environment are still being hindered due to inadequacy of rural road transport infrastructures. This situation has put the health of the rural dwellers in jeopardy and invariably makes them vulnerable to curable health challenges with known solutions in tertiary health centres in urban areas. Transport infrastructural challenges have made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Several authors have deliberated on numerous problems encountered by people living in rural areas, particularly in the area of mobility, which is very germane to the social and economic survival of any society. Gbadamosi & Olorunfemi (2016) stressed that road transport infrastructure appears to be an important concern for rural dwellers. Fatoke (2013) also observed that the provision of basic infrastructure in developing countries is more available in urban centres compared to what is available in rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have deliberated on numerous problems encountered by people living in rural areas, particularly in the area of mobility, which is very germane to the social and economic survival of any society. Gbadamosi & Olorunfemi (2016) stressed that road transport infrastructure appears to be an important concern for rural dwellers. Fatoke (2013) also observed that the provision of basic infrastructure in developing countries is more available in urban centres compared to what is available in rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In connection with the above, Adewole (2015) noted that roads remain one of the topmost facility of rural dwellers and must be at the centre of agricultural development policy. Gbadamosi & Olorunfemi (2016) are of the view that Nigeria is mainly a rural community bearing in mind that greater part of her population exists in the rural areas and deeply reliant on agriculture as the main source of occupation but are unfortunately faced with transportation challenges ranging from poor transport services, bad road condition, to poor road infrastructure among others. They affirmed that transport challenges encountered in the rural areas of Nigeria have been recognised as a key limitation to the actualisation of active food production, child and maternal healthcare delivery that are paramount to the sustenance of rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Akangbe et al (2013) reported that a lot of rural farmers in Kwara State Nigeria, express difficulties in income maximization from their agro-output as a result of poor road network. According to Gbadamosi and Olorunfemi (2016), rural Nigeria is yet to witness any rapid development despite process of economic liberation before the beginning of oil production as the provision of rural road infrastructures have been neglected. This has limited the level of agricultural activities of most farmers (Olorunfemi, 2018;Olorunfemi & Adenigbo, 2017) coupled with inadequate number of transit vehicles, recklessness and highway robbery (Nwafor & Onya, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The guiding questions to this research are: What is the electricity or energy experience of rural dwellers in Oyo state: And are there hopes of making use of rural renewable energy resources towards improving rural electricity access? Like all rural spaces which are poorly serviced (Gbadamosi and Olorunfemi, 2016;Brinkerhoff et al, 2016), rural households in Nigeria still remain in darkness due to a lack or sporadic access to electricity when compared to urban area (Sunderland et al, 2016). This limited rural access to electricity has been identified as one of the major limitations to the development of rural household capacity and the improved liveability of rural communities (Akuru et al, 2017).…”
Section: Introductionmentioning
confidence: 99%